2016
DOI: 10.3329/bjz.v43i2.27391
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis in Non-Endemic Districts of Bangladesh: Knowledge gap, Attitude and Practice of Inhabitants and Professionals for Treatment, Prevention and Control

Abstract: Investigation on knowledge, attitude and practice (KAP) of inhabitants and professionals for treatment, prevention and control of visceral leishmaniasis carried out on 519 inhabitants and 92 professionals of 6 districts (Panchagarh, Thakurgaon, Dinajpur, Bogra, Pabna and Shirajgonj) of Bangladesh. About 79.2% inhabitants agreed that they have heard about kala-azar disease. Regarding the transmission of kala-azar, 22.7% respondents answered by mosquito, about 38.3% said long period and irregular fever, 7.5% inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…Results of a study in Rajshahi district in 2008 showed that the frequency of VL was 27 times higher than the elimination target, the community people had poor knowledge on VL and its vector, and their health-seeking behavior was not acceptable [11]. Another study in non-endemic districts of Bangladesh during 2011–2012 reported that 65% of inhabitants were aware that kala-azar is curable, and only 13% heard of sandfly that indicates the poor awareness of the inhabitants regarding kala-azar [12]. A study in rural Fulbaria during 2015–2016 found that 100% of respondents heard about kala-azar, although only 0.93% were aware of sandfly [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of a study in Rajshahi district in 2008 showed that the frequency of VL was 27 times higher than the elimination target, the community people had poor knowledge on VL and its vector, and their health-seeking behavior was not acceptable [11]. Another study in non-endemic districts of Bangladesh during 2011–2012 reported that 65% of inhabitants were aware that kala-azar is curable, and only 13% heard of sandfly that indicates the poor awareness of the inhabitants regarding kala-azar [12]. A study in rural Fulbaria during 2015–2016 found that 100% of respondents heard about kala-azar, although only 0.93% were aware of sandfly [13].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about how individuals and communities in different areas of Bangladesh perceive the disease and its management [12, 13, 17], however, studies such as these are crucial for the appropriate use of limited resources in poor socioeconomic and educational conditions. The present study was, therefore, undertaken to assess the awareness of residents about kala-azar and related practices to control it in highly-endemic areas of Bangladesh.…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh has achieved remarkable success in improving maternal and child health due to a well‐organized health system involving both the public and private sectors, along with non‐government organizations (NGOs). The country has a plausible system of providing maternal and child health services from the primary level (i.e., sub‐district or union level health facility) to the highest level (i.e., national‐ or tertiary‐level health facility) 16 . Maternal services are organized through community clinics, health and family welfare centers, upazila or sub‐district health complexes, district‐level hospitals, tertiary‐level medical college hospitals, and specialized hospitals 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Three distinct clinically recognized leishmaniasis: Visceral leishmaniasis, cutaneous leishmaniasis and mucocutaneous leishmaniasis. 82 In 1824, a few Western doctors first described the kala-azar in Jessore district of Bangladesh where it was initially thought to be a form of malaria. Assam gave the name Assam fever.…”
mentioning
confidence: 99%